CLINICAL AND IMMUNOBIOCHEMICAL MARKERS AND THEIR CORRELATIONS IN PATIENTS WITH DEGENERATIVE-DYSTROPHIC DISEASES OF THE LUMBAR SPINE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Degenerative-dystrophic diseases of the lumbar spine are associated with impaired immunobiochemical homeostasis, requiring a comprehensive clinical and laboratory assessment. Purpose: To investigate the correlations between immunobiochemical and coagulation parameters in patients with degenerative lumbar spine disorders. Materials and Methods: A total of 102 patients were examined; serum levels of osteocalcin, β-CrossLaps, CRP, VEGF-A, TGF-β1, TNF-α, tPA, and PAI were analyzed along with coagulation indices (PT, APTT, TT, fibrinogen). Results: Significant correlations were revealed between inflammatory, angiogenic, and bone remodeling markers. Elevated CRP, VEGF-A, and TNF-α levels were associated with shortened coagulation times and hypercoagulable tendencies. Conclusion: The imbalance between inflammatory and coagulation systems plays a crucial role in the progression of degenerative spinal disorders.